Immunofluorescent visualization of mouse interneuron subtypes - Molgaard, Simon (F1000Res, 2014)
The activity of excitatory neurons is controlled by a highly diverse population of inhibitory interneurons. These cells show a high level of physiological, morphological and neurochemical heterogeneity, and play highly specific roles in neuronal circuits. In the mammalian hippocampus, these are divided into 21 different subtypes of GABAergic interneurons based on their expression of different markers, morphology and their electrophysiological properties. Ideally, all can be marked using an antibody directed against the inhibitory neurotransmitter GABA, but parvalbumin, calbindin, somatostatin, and calretinin are also commonly used as markers to narrow down the specific interneuron subtype. Here, we describe a journey to find the necessary immunological reagents for studying GABAergic interneurons of the mouse hippocampus. Based on web searches there are several hundreds of different antibodies on the market directed against these four markers. Searches in the literature databases allowed us to narrow it down to a subset of antibodies most commonly used in publications. However, in our hands the most cited ones did not work for immunofluorescence stainings of formaldehyde fixed tissue sections and cultured hippocampal neurons, and we had to immunostain our way through thirteen different commercial antibodies before finally finding a suitable antibody for each of the four markers. The antibodies were evaluated based on signal-to-noise ratios as well as if positive cells were found in layers of the hippocampus where they have previously been described. Additionally, the antibodies were also tested on sections from mouse spinal cord with similar criteria for specificity of the antibodies. Using the antibodies with a high rating on pAbmAbs, an antibody review database, stainings with high signal-to-noise ratios and location of the immunostained cells in accordance with the literature could be obtained, making these antibodies suitable choices for studying the GABAergic system.